2022
DOI: 10.1111/rda.14225
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous L‐arginine administration improves uterine vascular perfusion, uteroplacental thickness, steroid concentrations and nitric oxide levels in pregnant buffaloes under subtropical conditions

Abstract: Heat stress (HS) during pregnancy adversely affects uterine vascular perfusion and foetal development. L‐arginine (L‐Arg), a nitric oxide (NO) precursor, has been proven to enhance an organ's vascular perfusion. Therefore, this study aimed to examine the effect of L‐Arg administration on the pregnant buffaloes' uterine haemodynamics and uteroplacental thickness under environmental HS conditions. For this purpose, pluriparous (n = 12) HS‐pregnant buffaloes (mid‐gestation, 180–190 days; temperature humidity inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 68 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…These findings are in accordance with a previous study [ 38 ] that reported an increase in total arterial blood flow rate with advancement of gestational age in the control mares ( P = 0.0001). In this study, we reported a decline in both Doppler indices with pregnancy development; in addition, higher Doppler indices were observed in buffalo at 15 years old [ 19 ]. Finally, there was a negative correlation between uterine Doppler indices in all age jenny, as this means a marked elevation in the uterine vascular supply, especially in the left side.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings are in accordance with a previous study [ 38 ] that reported an increase in total arterial blood flow rate with advancement of gestational age in the control mares ( P = 0.0001). In this study, we reported a decline in both Doppler indices with pregnancy development; in addition, higher Doppler indices were observed in buffalo at 15 years old [ 19 ]. Finally, there was a negative correlation between uterine Doppler indices in all age jenny, as this means a marked elevation in the uterine vascular supply, especially in the left side.…”
Section: Discussionmentioning
confidence: 98%
“…Doppler studies of jenny gestational vessels, such as middle uterine and umbilical arteries, could give a prediction value of the gestation outcome [ 18 ]. It was reported that there was a monthly elevation of the uterine artery that led to a strong increase in blood flow rate and a marked decline in the RI during the first 8 months of pregnancy in buffalos [ 19 ].In addition, in mare the same declination in both Doppler indices was observed within gestational months [ 16 ], as this could be due to the presence of endothelial factors that were associated with the marked decline in both Doppler indices and related to arterial hypertension [ 17 ]. However, a study reported that uterine blood flow did not differ between pregnant and nonpregnant mares [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This data is significant in improving male dog productivity and reproductive pattern [52]. The improvement of testicular blood flow by the melatonin injection led to a mark in both Doppler indices parameters of the distal supra testicular arteries (PI and RI), which have a strong negative correlation with blood velocities parameters (PSV and EDV), testicular volume and intra-testicular colored areas [53][54][55]. The marked linear decline in both two Doppler indices leads to a substantial decrease in the blood flow resistance pattern and, therefore, an elevation of the testicular blood supply with an increase in sufficient nutrients and oxygen within both testes [56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen and nitrogen species (ROS and RNS) are produced during oxidative stress. They consist of hydroxyl radicals (OH), superoxide ions, hydrogen peroxide (H 2 O), and nitric oxide radicals (NO), which lead to lipid peroxidation, apoptosis, and infertility [3,4]. The impact of ROS and RNS on fertility is mediated by influencing folliculogenesis, steroidogenesis, and retained placenta [5,6].…”
Section: Introductionmentioning
confidence: 99%